Kultura społeczna Buriatów w polskich relacjach - Baranowski, Władysław (Zeszyty Wiejskie, 2012)
Among Polish authors writing about Buriats in the late 19th century and early 20th century there were those who paid special attention on the scila culture descriptions. First of all I should mention J.Kowalewski, A.Giller, J.Talko- Hryncewicz, B.Dybowski, P.Smolik. On one hand they focused on the social structure and on the pother hand they were interested in family life of Buriats, rising the children and the position of women. The mentioned authors focused on family rituals, describing the functioning habits closely connected to wedding and funeral ceremonies.